Antifatigue Activity of Citrullus (Citrullus lanatus) Genus Plant: A Review - Wahyuni, I (KnE Life Sciences, 2019)
Watermelon (Citrullus lanatus, the family of cucumber or Cucurbitaceae) is a vine that originates from a half-desert region in southern Africa. This plant is still close to pumpkin (Cucurbitaceae), melon (Cucumis melo) and cucumber (Cucumis sativus). Empirically this plant is useful for reducing fatigue. In addition, its health benefits can reduce fever, smooth urine, antihypertension, increase body immunity, etc. Watermelon is rich of electrolyte content, so that sweat, body fluids that have been lost during vomiting or during activity will be replaced by watermelon juice taken. Nearly 92% of the watermelon content is water, and the content of folate is 3 mcg / 100 g of watermelon which is needed during the early trimester of pregnancy for the formation of the brain and fetal nerves. Antioxidants and vitamin C help the body maintain health, can launch and stimulate urine, be good for the kidneys, reduce fever and prevent thrush, ward off carcinogenic free radicals because of its lycopene content. The purose of this paper is to examine the anti fatigue activity of the citrullus genus plant bases on scientific data. The method used in this study is the literature’s study. Searching for scientific data is done online (in the PubMed database, Science Direct and Google Scholar) and various books (Indonesian Herbal Pharmacopoeia and PROSEA). Keywords: citrullus genus, anti fatigue Activity, invivo, invitro